Relationship between Marital Commitment and Marital Satisfaction with Self-Conscious Emotions and Self-Coherence married female - Moghadamnia, Mohammad Mehdi; Soleimani Farsani, Bentol Hoda (Psychology of Woman Journal, 2023)
Objective: This research aimed to examine the relationship between marital commitment and marital satisfaction with self-conscious emotions and self-coherence. Method: A descriptive correlation design was adopted. The sample consists of 160 married female students aged 20 to 65 years studying in Islamic Azad University in Tehran, selected by available method. Data collection tools included the Marital Commitment Questionnaire (MCQ), ENRICH Marital Satisfaction Scale (EMS), the Test of Self-Conscious Affect (TOSCA), and the Sense of Coherence Scale (SOC). Data were analyzed using Pearson correlation coefficient tests and multiple regression analysis.Results: The results showed that the self-conscious emotion of shame has a significant negative relationship with marital commitment and marital satisfaction of married women (p